Determinants of Intellectual Capital Performance (Empirical Study: Indonesian Syariah Bank 2010-2015) - Hidayah, Karimatul Hidayah; Ade Adityawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
The purpose of this research is to examine the determinants of intellectual capital performance in Indonesia's syariah banks over period 2010-2015. Multiple regression analysis is used to test the relationship between the independent variable and the dependent variable-intellectual capital performance. The value added intellectual capital (VAIC) developed by public is used to measure the intellectual capital performance in Indonesia's syariah banks. Results indicate that market concentration level as the independent variable has a positive and significant relationship with the intellectual capital performance. The other independent variable, bankprofitability and bank risk, has a negative influence to the intellectual capital performance. Meanwhile, barriers to entry in the corporate sector, bank size, and bank size are not significantly influencing the intellectual capital performance. There are several measurement of intellectual capital performance such as public (VAIC) , VAIC modification by Ulum (M-VAIC), or Tobin-Q. Those methods difference lower the research validity. This research may give information related to the determinants of intellectual capital performance for syariah banks in order to take it as the consideration in making operational decision. This research is the first research that tests the determinants of intellectual capital performance in Indonesia's syariah banks over the period 2010-2015.